STUDENTS’ CONSTRAINTS IN READING DESCRIPTIVE TEXT AT MTs USWATUN HASANAH - Novia Wulansari; Sri Supiah Cahyati (IKIP Siliwangi, 2021)
The aim of the research was to investigate the constraints and ability in Reading comprehension. This research was qualitative research. The subjects were 20 students of Class VII A of MTs Uswatun Hasanah, and they were divided into two groups based on their score. The students getting score above the standard score were grouped in group A; and those getting score under the standard score were in group B. To gain the data, the study employed the Reading test and as the instruments. The data were analyzed by using descriptive analysis. The finding revealed that there was only one student getting high score (above the standard score), while 19 students got low score (under the standard score). Furthermore, the Reading comprehension ability between the students of group A and B was not significantly different and their constraints were relatively similar.Keywords: constraints, descriptive text, reading comprehension